Factors related to the long-term effect and condition to child abuse: a preliminary study - Suvitra Ravi; Luh Nyoman Alit Aryani; Lely Setyawati Kurniawan (Intisari Sains Medis, 2021)
Background: Child abuse is any behavior that harms a child under 18 years old. It can take many forms, including physical, sexual and emotional abuse, as well as neglect. This study aims to determine factors related to child abuse's long-term effect and condition as a preliminary study.Methods: A cross-sectional study was conducted among 73 students out of 232 students from Semester 7. They have been approached and have been explained this research. The age of students must be more than 18 years old, from both genders who are pursuing their studies in Medical Faculty of Universitas Udayana. Data were analyzed using SPSS version 20 for Windows.Results: Most of the respondents were age 21 years old (58.9%), female (67.1%), strongly disagree with physical abuse (41.1%), sexual abuse (63.0% and 60.3%), emotional abuse (39.7% and 37.0%), and child neglect (68.5%).  Most of several conditions that students disagree with the long term effect of child abuse are sleep at night (38.4%), nightmare problems (43.8%), breathing problems (47.9%), loneliness (27.4%), fears of people judgment (28.8%), as well as fear and anxiety issue (39.7%).Conclusion: The medical students strongly disagree with many kinds of child abuse and disagree with several factors related to child abuse's long-term effect.